Cystic fibrosis microbiology: advances in antimicrobial therapy - Waters, Valerie; Smyth, Alan R. (Elsevier, 2015)
Much of the improvement in the survival of individuals with cystic fibrosis (CF) is due to advancements in antimicrobial treatments. New aerosolized antibiotic formulations have recently been introduced (such as inhaled aztreonam), and others are in development (inhaled levofloxacin and liposomal amikacin). Licensed dry powder formulations include tobramycin inhalation powder and dry powder colistimethate (available in Europe). Although inhaled antibiotics have the advantage of being able to deliver high intrapulmonary concentrations of drug, antimicrobial resistance can still develop and is a concern in CF. Antimicrobial resistance might be mitigated by using non-antibiotic treatments, antibiotic adjuvants, which have activity against bacteria. Examples include agents such as gallium, antimicrobial peptides and anti-biofilm compounds such as alginate oligosaccharides (OligoG) and garlic. Vaccination strategies and antibody therapy (IgY) against Pseudomonas aeruginosa have also been attempted to prevent initial infection with this organism in CF. Although aggressive and long-term use of antibiotics has been crucial in slowing lung function decline and improving survival in people with CF, it has added a significant burden of care and associated toxicities in these individuals. Careful surveillance and the use of preventative strategies for antibiotic related toxicity (such as nephrotoxicity and ototoxicity) are essential. Continued development of effective antimicrobial agents that can function in the conditions encountered in the CF lung, such as against bacterial biofilm growth and under anaerobic conditions, is needed.